Self-assembly of graphene-encapsulated antimony sulfide nanocomposites for photoredox catalysis: boosting charge transfer via interface configuration modulation. (15th August 2019) - Zhang, Bei-Bei; Huang, Ming-Hui; Dai, Xiao-Cheng; Li, Tao; Li, Yu-Bing; Hou, Shuo; He, Yunhui; Xiao, Guangcan; Xiao, Fang-Xing
Abstract : Charge transfer over Sb2 S3 –GR nanocomposites was tuned by exquisite interface configuration engineering, which results in enhanced photoredox performances under visible light irradiation. Abstract : Recent years have witnessed an explosive investigation on the construction of graphene (GR)–semiconductor composite photocatalysts, but the specific correlation of the interface integration mode between GR and a semiconductor with the interfacial charge transfer characteristics is yet to be clearly clarified. To this end, a facile, green and surface linker-triggered self-assembly has been designed to construct GR-encapsulated antimony sulfide nanorod (Sb2 S3 NRs–GR) ensembles, wherein tartaric acid-capped intrinsically negatively charged Sb2 S3 NRs and surface-modified positively charged GR nanosheets were utilized as the building blocks. It was unveiled that the exquisitely designed interface configuration afforded by the intimate encapsulation of Sb2 S3 NRs with GR via an electrostatic/hydrogen interaction is beneficial for fully harnessing the structural merits of GR in boosting light absorption, increasing the specific surface area and accelerating the interfacial electron transfer kinetics. Thus, the lifetimes of the photogenerated charge carriers were synergistically prolonged over Sb2 S3, resulting in the considerably enhanced visible-light-responsive photoredox performances of the Sb2 S3 –GR nanocomposites toward the photoreduction of heavy metal ions and mineralization of organic pollutants compared with the blank Sb2 S3 and nanocomposite counterpart without a finely tuned interface. More importantly, the crucial role of interface configuration between GR and the Sb2 S3 NRs in dictating the interfacial charge transfer efficiency was substantiated. In addition, the predominant active species in the photoredox catalysis were determined and the corresponding photocatalytic mechanism was elucidated. Our work sheds light on mediating the interfacial charge transfer via rational interface configuration modulation toward substantial solar energy conversion.